2014
DOI: 10.1016/j.mmcr.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Malassezia pachydermatis fungemia in a preterm neonate resistant to fluconazole and flucytosine

Abstract: A case of Malassezia pachydermatis fungemia in a preterm neonate is described. The isolate was identified by rDNA sequencing and was resistant to fluconazole and flucytosine. Since M. pachydermatis does not require lipid supplementation for growth, it can be misidentified as a Candida species. The report highlights M. pachydermatis as a cause of late onset sepsis in preterm neonates and emphasizes the need for prior antifungal susceptibility testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Our assay included the echinocandin class as well as griseofulvin. The data showed that Malassezia is resistant to these antifungals, which is in line with literature reports (3,23). The azoles itraconazole, posaconazole, and voriconazole appeared to be the most effective antifungals against Malassezia spp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our assay included the echinocandin class as well as griseofulvin. The data showed that Malassezia is resistant to these antifungals, which is in line with literature reports (3,23). The azoles itraconazole, posaconazole, and voriconazole appeared to be the most effective antifungals against Malassezia spp.…”
Section: Discussionsupporting
confidence: 92%
“…Malassezia is the most common fungal genus of the healthy human skin microbiome (2). Additionally, a pathogenic role is attributed to these yeasts in common skin diseases such as pityriasis versicolor, atopic dermatitis, and seborrheic dermatitis, and they can cause severe systemic infections in neonates and immunocompromised individuals (3,4).…”
mentioning
confidence: 99%
“…Their incidence seems to be higher in some autoimmune disorders, such as psoriasis or atopic dermatitis (1012). Although rare, some cases of fungemia and other invasive infections (peritoneal and biliary infections) (13, 14) have been described since the 1980s (1315). These infections have no specific clinical signs and therefore remain difficult to diagnose.…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal susceptibility of Malassezia species using agar and broth dilution alternative methods has been studied . Currently, few antifungal susceptibility tests are performed using disc diffusion methods, but only when studying the non‐lipid‐dependent species, M. pachydermatis …”
Section: Introductionmentioning
confidence: 99%